Fish remnants from the excavations of the Bronze Age barrow near Maryanskoe village (Dnepropetrovsk region, Ukraine) - O. M. Kovalchuk (Vìsnik Dnìpropetrovsʹkogo Unìversitetu: Serìâ Bìologìâ, Ekologìâ, 2014)
The Bronze Age mound (2.5–2.3 kya BC) is located near the Maryanskoe village (Apostolovskyi district, Dnepropetrovsk region) and was excavated in 1953. The results of determination of the fish remnants, which were found during the excavation, are presented in the paper. Eleven species belonging to 9 genera, 5 families and 5 orders (Acipenseriformes, Cypriniformes, Siluriformes, Esociformes, Perciformes) were identified: russian sturgeon Acipenser gueldenstaedtii Brandt et Ratzeburg, 1833, stellate sturgeon A. stellatus Pallas, 1771, common ide Idus idus (Linnaeus, 1758), common roach Rutilus rutilus (Linnaeus, 1758), pontic roach R. frisii (Nordmann, 1840), common bream Abramis brama (Linnaeus, 1758), common carp Cyprinus carpio Linnaeus, 1758, tench Tinca tinca (Linnaeus, 1758), european catfish Silurus glanis Linnaeus, 1758, northern pike Esox lucius (Linnaeus, 1758), and zander Sander lucioperca (Linnaeus, 1758). Most of them are quite common in the Dnieper river basin. It was found that carp fishes predominate in the number of species. Most of the bone remnants in the collection belong to zander, catfish and pike, while common roach, pontic roach and common bream are identified by the few bones. This may indicate a different role of these species in the diet of the local population. The ratio of skeletal elements in the collection is the evidence of the fish cutting on the site. Body length and weight was reconstructed for 64 fish specimens. It was found that they were mature and small-sized, except for catfish, pike and perch. Taking into account the characteristics of the funeral rituals of the Yamna culture population, fish bones from the mound near Maryanskoe can be remnants of the parting meal.